Peranan social capital dalam memelihara keberlanjutan agribisnis jagung - Jajat Sudrajat; Jangkung Handoyo Mulyo; Slamet Hartono; Subejo Subejo (Masyarakat, Kebudayaan dan Politik, 2015)
Study the role of social capital on nurturing of agribusiness sustainability is still limited. Whereas, the indepth understanding toward the role of social capital in facilitating cooperation on relationships among institutions (actors) of agribusiness is very important and strategic for planning of agricultural development. This study is aimed to describe the role of social capital in facilitating cooperation on relationships among marketing institutions of corn in Tujuh Belas sub district, Bengkayang regency. The primary data were collected by observation, focus group discussion, and indepth interview to farmers and traders. The result of this study shows that the implementation of social capital element in farming activities or agribusiness in this location, generally based on effort of resources exchange among actors. On the relationships among the farmers, social capital is implemented by exchange of household labor (strict and sort term reciprocity). Meanwhile, in relationships between farmer and village trader and also between village trader and wholesaler, the social capital is implemented by exchange of economic resources. The exchange of resources is frequent implemented by trial risk, risk sharing, and applying flexibility in any type of transaction (non strict reciprocity in the sort term). This resources’s exchange is understood as effort to nurture agribusiness sustainability in the long run.